Reconstructing the Concept of Murāja‘ah in QS. al-Qiyāmah [75]: 16–19: A Tafsīr Analysis of the Mechanism of Revelation Reception and Preservation - Diki Saputra Siregar; Tryadi, Pajar Tryadi; Mardian Idris Harahap; Rahayu Fuji Astuti (AL-DZIKRA: JURNAL STUDI ILMU AL-QUR'AN DAN AL-HADITS, 2026)
Abstract This study examines the mechanism of revelation reception and preservation in QS. al-Qiyāmah [75]: 16–19, focusing on the reconstruction of the concept of murāja‘ah from the perspective of Islamic epistemology. The study is motivated by the tendency of previous research to position murāja‘ah primarily as a method for maintaining Qur'anic memorization, without examining its conceptual foundation in the Qur'an itself. This research employs a qualitative approach based on library research, using a tafsīr case study method on QS. al-Qiyāmah [75]: 16–19. The data were analyzed by examining asbāb al-nuzūl, linguistic aspects, and comparing interpretations by classical and contemporary exegetes, particularly al-Ṭabarī, Ibn Kathīr, and al-Qurṭubī. The findings show that this sequence of verses contains four main components of the revelatory process: the prohibition against hastily receiving revelation, the guarantee of its compilation (jam‘), recitation (qirā’ah), and explanation (bayān). These four components form an epistemological system that ensures the authenticity and proper understanding of revelation. Based on these findings, murāja‘ah is reconstructed not merely as an form of repetitive memorization but as a mechanism that encompasses the reception, retention, and reproduction of knowledge. This study contributes to the theoretical understanding of murāja‘ah and offers a conceptual foundation for more reflective and sustainable Qur'anic learning. Keywords: Islamic epistemology; Murāja‘ah; Tafsir Studies.   Abstrak Penelitian ini mengkaji mekanisme penerimaan dan pemeliharaan wahyu dalam QS. al-Qiyāmah [75]:16–19 dengan fokus pada rekonstruksi konsep murāja‘ah dalam perspektif epistemologi Islam. Kajian ini dilatarbelakangi oleh kecenderungan penelitian sebelumnya yang memposisikan murāja‘ah sebagai metode menjaga hafalan Al-Qur’an, tanpa mengkaji dasar konseptualnya dalam Al-Qur’an. Penelitian ini menggunakan pendekatan kualitatif berbasis studi kepustakaan dengan metode studi kasus tafsir terhadap QS. al-Qiyāmah [75]:16–19. Data dianalisis melalui penelaahan asbāb al-nuzūl, aspek kebahasaan, serta komparasi penafsiran mufasir klasik dan kontemporer, terutama al-Ṭabarī, Ibn Kathīr, dan al-Qurṭubī. Hasil penelitian menunjukkan bahwa rangkaian ayat tersebut memuat empat komponen utama mekanisme pewahyuan, yaitu larangan tergesa-gesa menerima wahyu, jaminan penghimpunan (jam‘), pembacaan (qirā’ah), dan penjelasan (bayān). Keempat komponen tersebut membentuk sistem epistemologis yang menjamin otentisitas dan pemahaman wahyu. Berdasarkan temuan tersebut, murāja‘ah direkonstruksi tidak hanya sebagai aktivitas pengulangan hafalan, tetapi sebagai mekanisme yang mencakup resepsi, retensi, dan reproduksi pengetahuan. Penelitian ini berkontribusi pada pengembangan pemahaman teoretis tentang murāja‘ah serta menawarkan landasan konseptual bagi pengembangan pembelajaran Al-Qur’an yang lebih reflektif dan berkelanjutan. Kata Kunci: Epistemologi Islam; Murāja‘ah; Studi Tafsir.